Nigeria Labour Handbook - Federal Ministry of Employment, Labour and Productivity Lagos; Federal Ministry of Employment, Labour and Productivity (Lagos, Nigeria : Federal Ministry of Employment, Labour and Productivity Lagos, 1991)
This book contains information on the activities of the Federal Ministry of Employment, Labour and productivity in Nigeria from inception to date.
Includes index
gau 31/08/2016
Loans
Keywords: Labour activities; Nigeria